DETERMINAN RISIKO SISTEMATIS DAN KINERJA SAHAM PADA SEKTOR INDUSTRI BARANG KONSUMSIDI BURSA EFEK INDONESIA - Rahmawati Rahmawati (Universitas Mercu Buana, 2015)
Abstract. This research is intended to know how big the influences of fundamental ratio,market ratio, business performance and macro-economic to the systematic risk and theirImpacts to the performance on shares at the Consumer goods industry which listed atIndonesia stock exchange. The sampling method used was purposive sampling technique.From population of 37 companies, 16 companies met the criteria to the sample. Data in thisresearch are collected by using the method of documentation study and documents ofcompanies in the Consumer goods industry sector with the sources deriving from FinancialStatements of companies listed at Indonesia Stock Exchange for the period 2010-2014. Datais analyzed by using partial least square modeling processed through the Smart PLS softwareof 3.0 versions.Output of this study indicates that the fundamental ratio and market ratio havesignificant influence, but business performance, macro-economic do not have significantinfluence to the systematic risks, Further, fundamental ratio, market ratio and businessperformance do not have significant influence as well to the performance on shares, but on thecontrary the macro-economic has significant to performance on shares. Fundamental ratio,market ratio, business performance and macro-economic to the systematic risk and there isn‟tany significant Impacts to performance on shares.Keywords: Business performance, Fundamental ratio, Macro-economic, Market ratio, Partialleast square, Performance on shares, Systematic risk